The Effect Of Corporate Governance, Company Size On Financial Statement Fraud In Banking Companies - Kurnia, Zirda; Yuliusman, Yuliusman; Yustien, Reni (Jurnal Cakrawala Akuntansi, 2023)
This research entitled the effect of corporate governance and firms size to financial statement fraud in banking companies on Indonesia Stock Exchange in period 2014-2018. There is a scandal (gap fenomenon) in financial companies relate to the manipulation financial statement that occurred in 2018. Some of the supported studies conducted research on the effect of corporate govenance and firms size to financial statement fraud of the results in this research show conclusions that are relatively inconsistent with each other (research gap). This research aimed to determine empirically the effect of corporate governance and firms size to financial statement fraud in banking companies on Indonesia Stock Exchange in period 2014-2018. The population in this research are banking companies on Indonesia Stock Exchange in period 2014-2018. The sampling method used is purposive sampling with the number of samples is 35 companies. The analysis method use in this research is multinomial logistik regression with SPSS software version 22.0 for windows. The result of this research concluded that (1) the board of commissioners, independent commissioners, audit committees, the effectiveness of internal audit, and firms size simultaneously have effect to fraudulent financial statements (2) the board of commissioners, independent commissioners, and firms size partially have affect to fraudulent financial statements (3) audit committees and the effectiveness of internal audit have no effect to fraudulent financial statements.